Analisis Kemampuan Pegawai, Motivasi Kerja Dan Iklim Organisasi Dengan Kinerja Pegawai Dinas Pendidikan, Kebudayaan, Dan Pemuda Olahraga Kabupaten Semarang - Anggarwati, Meity Sri; Nurchayanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
This research aims to find out the correlation between employee ability, work motivation and organizational climate with the performance employee in the Dinas Pendidikan, Kebudayaan, dan Pemuda Olahraga in Semarang Regency. Respondents in this research is 51 employees of Dinas Pendidikan, Kebudayaan, dan Pemuda Olahraga in Semarang Regency. The data analysis method used Kendall Tau correlation coefficient to find out how much the correlation between each independent variables with dependent variables, Kendall concordance correlation to find out how much the correlation between all independent variables together with dependent variables, and the coefficient of determination to know how much the percentage of influence three independent variables on employee performance. The results of the research is show the conclusion that, 1) there is a positive and significant correlation between employee ability on employee performance (r = 0.619), 2) there is a positive and significant correlation between work motivation on employee performance (r = 0.578), 3) there is a positive and significant correlation between organizational climate on employee performance (r = 0.628), 4) there is a positive and significantly correlation between all employee ability, work motivation, and organizational climate together has correlation on employee performance by 0.883, and 5) employee ability, work motivation, and organizational climate has the correlation that affects employee performance by 74.9% is indicated by the coefficient of determination R2 = 0.749.